Pengaruh Keputusan Pendanaan dan Keputusan Investasi Terhadap Nilai Perusahaan dengan Kebiijakan Dividen Sebagai Variabel Intervening Pada Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia - Nyayu Khairani Putri; Isnurhadi Isnurhadi; Yuliani Yuliani (MediaTrend, 2018)
The purpose in this research is aims the influence funding decision and investment decision on the value of the company with dividend policy as intervening variables on manufacture company at Indonesian Stock Exchange. Sample in this study were 50 companies in manufacture sector in period 2013-2016. Samples were chosen by using purposive sampling. Data were analyzed by using path analysis. The result of the research showed; funding decision (DER), investment decision (MBVA), and dividend policy (DPR) has positive and significant effect on the value of the company (PBV). Funding decision (DER) have negative and significant effect on dividend policy (DPR). Investment decision (MBVA) has positive and significant effect on dividend policy (DPR). Dividend policy (DPR) is able to partial mediation the effect of funding decision (DER) and investment decision (MBVA) on the value of the company (PBV).